2013
DOI: 10.1021/es4027024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Permanganate Preoxidation and Preozonation on Algae Containing Water: Cell Integrity, Characteristics, and Chlorinated Disinfection Byproduct Formation

Abstract: Aqueous suspensions of Microcystis aeruginosa were preoxidized with either ozone or permanganate and then subjected to chlorination under conditions simulating drinking water purification. The impacts of the two oxidants on the algal cells and on the subsequent production of dissolved organic matter and disinfection byproducts were investigated. Preozonation dramatically increased disinfection byproduct formation during chlorination, especially the formation of haloaldehydes, haloacetonitriles, and halonitrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(103 citation statements)
references
References 45 publications
5
91
0
4
Order By: Relevance
“…1). A previous study also reported that cell damage induced by elevated oxidant dose could promote protein and amino acid release (Xie et al, 2013). In addition, the proteins were mainly released during the preoxidation period, and prolongation of simulated transportation time did not have an obvious influence on the protein concentrations.…”
Section: Aom Release After Prechlorination During Simulated Transportmentioning
confidence: 73%
See 1 more Smart Citation
“…1). A previous study also reported that cell damage induced by elevated oxidant dose could promote protein and amino acid release (Xie et al, 2013). In addition, the proteins were mainly released during the preoxidation period, and prolongation of simulated transportation time did not have an obvious influence on the protein concentrations.…”
Section: Aom Release After Prechlorination During Simulated Transportmentioning
confidence: 73%
“…The initial DOC value in the prepared algal suspension was determined to be 0.27 mg/L, which might be due to the desorption of the loosely bound AOM on the cells (Xie et al, 2013). The increased DOC and DON values with prolongation of simulated transportation time were due not only to the further release of AOM from cyanobacterial cells damaged by prechlorination, but also to the rising ratios of damaged cells (Fig.…”
Section: Aom Release After Prechlorination During Simulated Transportmentioning
confidence: 94%
“…Prior to Fe(II) addition, KMnO 4 can react with the organic matter, such as the dissolved organics and the surface-absorbed AOM on algae cells (Eq. (1)) (Xie et al, 2013). The surface-absorbed AOM serves as a protective barrier to stabilize the algae cells, and this effect enhances the difficulty of removing algae cells by conventional processes (Clasen et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…KMnO 4 pre-oxidation [8] can enhance algal cell removal and control chlorinated DBPs. The impacts of O 3 on coagulation for NOM and DBP precursor removal are conflicting and site specific [9,10].…”
Section: Introductionmentioning
confidence: 99%